Al-'Arad al-Qur'ani wa-al-Hadithi li-qissati liqa' Musa 'alaihi al-salam ma'a al-Khidir fi Surat al-Kahf - Sarina Bt 'Abd al-Ghani (Kolej Universiti Islam Malaysia, 2014)
This research is about the presentations of Quran and Sunnah, which showed that in "Surah Al-Kah fi (Grave)". From this discussion we had been revealed that truth of Khidr's behaviours from Quran and Sunnah. The analysis had been focus on meeting between Musa and Khidr. The impression about this story is also tried to evident reader to find out data through Musa and Khidr communicated. To fulfil this Academic Project, the writer had used the Inductive Method and the Descriptive Method to obtain sources, references and other all width.